Genomic Characterization of CIAV Detected in Contaminated Attenuated NDV Vaccine: Epidemiological Evidence of Source and Vertical Transmission From SPF Chicken Embryos in China - Li, Yan; Wang, Jinjin; Chen, Longfei; Wang, Qun; Zhou, Meng; Zhao, Hui; Chi, Zengna; Wang, Yixin; Chang, Shuang; Zhao, Peng (Frontiers in Veterinary Science, 2022)
Live attenuated vaccines have been extensively used to prevent infectious disease in poultry flocks. However, exogenous virus contamination in attenuated vaccines had been reported several times in the past, which brought huge economic losses to poultry farming and vaccine production. Recently, attenuated Newcastle disease virus (NDV) vaccines were detected to be contaminated with chicken infectious anemia virus (CIAV) in a routine screening for exogenous viruses. To investigate the possible source of the contamination, blood samples of a specific-pathogen-free (SPF) layer breeder flock were collected, and the serum antibody to viruses were detected by enzyme-linked immunosorbent assay (ELISA). Then, 14 to 18 day old SPF chicken embryos (n=40) were randomly selected for determination of CIAV contamination. Tissue DNA was extracted from the SPF chicken embryos and detected by molecular virology assays. These results showed that SPF chickens and embryonated eggs used for vaccine preparation were CIAV-positive. The full-length genome of CIAV was sequenced and designated SDSPF2020 (Genbank accession number: MW660821). The sequences of CIAV from SPF embryos and NDV vaccines consisted of 2,298 nucleotides (nt) with 100% homology. Data showed 95.8%-99.6% homology with the complete nucleotide sequences of reference strains, and shared the highest sequence identities to the Chinese strain HLJ15125. This study illustrated that vertical transmission of CIAV from a SPF layer breeder flock to embryos was a nonneglible way for exogenous virus contamination in vaccine production.